Identifikasi Jenis Ikan Hasil Tangkapan Nelayan Pantai Utara (Pantura) di Provinsi Jawa Timur - Muhammad Nur Arkham; Mathius Tiku; Agus Ramli; Arif Trihandoyo (Journal of Aceh Aquatic Sciences, 2021)
The fisheries management area on the North Coast of East Java is included in WPP 712 which covers the Java Sea. Potential fish resources in WPP 712 include demersal and small pelagic fish resources. The purpose of this study was to inventory data on the dominant types of fish caught by fishermen who landed their catch along the North Coast of East Java. The research method used is survey method and direct observation. Some of the places that became the sampling area were the Fish Landing Base (PPI) Kranji (Lamongan Regency), Banyusangka Fish Landing Base (PPI) (Bangkalan Regency), PPI Ketapang (Sampang Regency), PPI Tamberu (Pamekasan Regency) and the Port and Resource Management Unit. Pasongsongan Marine and Fisheries (Sumenep Regency). The data taken in this study included the morphometric, color and meristic characteristics of each identified fish species. Based on the results of the study, it showed that most types of fish caught by fishermen on the North Coast of East Java were dominated by the Carangidae family which contained 6 fish species and the Scrombidae family which contained 3 fish species.